Environmental Accounting Disclosure and Economic Value of Listed Agricultural Firms in Nigeria - Awotomilusi, Niyi Solomon; Dagunduro, Muyiwa Emmanuel; Olipede, Dare Ezekiel; Owolabi, Olufemi Adebola; Adeyemo, Soji Tobi; Ajayi, Olabisi Abiodun; Adewole, Isiaka Adesoji (International Journal of Economics and Financial Issues, 2025)
This study investigated the nexus between environmental accounting disclosure and economic value of listed agricultural firms in Nigeria. This study employed ex-post facto research design, and data collected from the annual reports and sustainability disclosures of agricultural firms listed on the Nigerian Exchange Group (NGX) as at 31st December, 2023. The population was comprised of 5 agricultural firms listed on the NGX and the study adopted a census sampling technique to include the entire population. The study covered a 10-year period, from 2014 to 2023, consisted of the transition of the Nigerian Stock Exchange (NSE) to the Nigerian Exchange Group (NGX). Descriptive statistics were used for data analysis. Through the regression analysis conducted, this study found that environmental accounting disclosure had a positive and significant effect on the economic value of these firms. This suggests that environmental transparency and accountability enhance the financial performance of agricultural firms in Nigeria. This study concluded that environmental accounting disclosure is an important factor in improving the economic value of listed agricultural firms in Nigeria. It is therefore important for agricultural firms in Nigeria to enhance their environmental reporting practices to provide more comprehensive and transparent information about their environmental impact.